Implementasi Peraturan Daerah No. 02 Tahun 2012 dalam Mendukung Keberlanjutan dan Daya Saing Pasar (Studi Pada Pasar Semampir Kabupaten Probolinggo) - Sucahyo, Imam; Maksin, Mastina; Setyowati, Irma Nur Cahya (Innovative: Journal Of Social Science Research, 2025)
Traditional markets play a vital role in supporting the local economy and preserving cultural heritage. This study aims to analyze the implementation of Regional Regulation No. 02 of 2012 Article 6 &7, with a case study at Semampir Market, Probolinggo Regency. The research adopts a qualitative approach using case study methods. Data were collected through observation, interviews, and documentation. The findings reveal that the regulation's implementation remains suboptimal due to issues such as inadequate supervision, insufficient infrastructure, and competition from modern markets. Nevertheless, efforts from local governments and stakeholders have been made to improve market management and competitiveness. A more integrated strategy is needed to establish sustainable and competitive traditional markets. Keywords: traditional market, regional regulation, empowerment, policy implementation